The best choice for locomotion in mountain environment: walking, running or cycling? - Ardigo, L. P.; Saibene, F.; Minetti, A. E. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
On a level ground, cycling (B) is more economical than running (R), which in turn is more economical than walking (W) in a high speed (v) range. This study investigates whether this ranking still holds in locomotion in mountain environment, where the three modes are expected to be mainly facing the same burden, i.e. to contrast gravity. Methods: By using data from the literature (Margaria, 1938; di Prampero, 1986 and 2000), we have built a theoretical framework to predict the optimal mode as a function of the gradient (i). To verify the prediction, seven amateur bikers were then asked to walk, run and ride on a treadmill at different gradients. The speed was set as to maintain almost constant the metabolic demand across the different gradients. Finally, one subject has been loaded during bipedal gaits with a bicycle-equivalent mass, to simulate a cross-country cycling situation. Results: By means of the model, B was found to be the mode of choice only below 10-15% gradient, while above it W was the least expensive locomotion type. This is depicted in the left figure, where the metabolically feasible v-i zone is coloured darker (for an available maximum aerobic power . 10 W/kg). This surface corresponds to the metabolically optimal mesh of the cost (C) vs. v-i relations for the three investigated gaits submitted to the constraint of . The other two interrupted curves represent boundaries for 6 and 14 W/kg. The laboratory results indicate that the "critical slope", i.e. the one above which W is less expensive than B (and R), is about 13-15%. This is depicted in the right figure, where C, for vertical distance travelled, is plotted as a function of i. Vertical bars represent standard errors, for sake of graphical convenience, and the asterisks indicate a statistical significant difference (* p<0.05, ** p<0.01) between the two least expensive locomotion modes at the gradients where at least 4 subjects were able to perform them. Each data series has been fitted by a 2 fV&O2Max fV&O2Max and order polynomial curve. The dashed horizontal line represents C of pure work against gravity, i.e. the mechanical work necessary to increase the body potential energy, assuming an efficiency for positive work equal to 0.25. That line constitutes the minimum metabolic of gradient locomotion (thus no experimental point is expected to fall in the grey area below it). The middle and upper horizontal lines reflect the vertical C for lower efficiencies of the potential work: 0.20 and 0.15, respectively). With the subject loaded, the critical slope resulted to be close to 20%, due to the higher C of loaded W and R. Conclusion: Both the prediction and the laboratory verification showed that in mountain environment only W and B survive the competition for the metabolically optimal gait, with the second preferable at low i. To have expressed the C "per vertical displacement" allowed a better comparison between the investigated gaits. Part of the resulting metabolic differences can be explained by the various mechanics. At i >15% W and R surely stop wasting energy into negative work, while B keeps being relatively expensive due to extra energy likely required to sustain low v and high i pedalling.